Meeting places against the background of loneliness - Lidin, Konstantin (project baikal, 2024)
Meetings in themselves were perceived as a positive phenomenon until the seventies of the twentieth century. Since the last quarter of the last century, there has been a growing ‘epidemic of loneliness’. Today, a large part of the society, especially in wealthy Western countries, has lost the skills of meeting and has become accustomed to loneliness. This trend is reflected in modern architecture and urban planning in the form of strong trends of segregation and ghettoisation of cities, as well as in the construction of small houses for solitary living. The negative effect of the spread of loneliness and the ways to overcome this trend are shown.
Keywords: architecture; urbanism; meeting places; loneliness; sociology; psychology